Spotlight on Faricimab in the Treatment of Wet Age-Related Macular Degeneration: Design, Development and Place in Therapy - Nair AA; Finn AP; Sternberg P Jr (Dove Medical Press, 2022)
Archana A Nair, Avni P Finn, Paul Sternberg Jr Vanderbilt Eye Institute, Vanderbilt University Medical Center, Nashville, TN, USACorrespondence: Paul Sternberg Jr, Chair and G. W. Hale Professor of Ophthalmology and Visual Sciences, Vanderbilt Eye Institute, Vanderbilt University Medical Center, 2311 Pierce Avenue, Nashville, TN, 37232, USA, Email Paul.sternberg@vumc.orgAbstract: The advent of anti-vascular endothelial growth factor (VEGF) agents has revolutionized the treatment of retinal neovascular diseases including neovascular age-related macular degeneration (nAMD), a leading cause of irreversible blindness. Multiple agents and methods for drug delivery are emerging to increase the duration of treatment effect and treatment interval, reducing the overall treatment burden on patients and clinicians. The newest agent on the market is faricimab. This medication targets two distinct pathways in retinal angiogenesis, VEGF-A and Ang-2, to create a more durable effect. Phase 3 trials for this drug compared treatment intervals up to 16 weeks against aflibercept dosed at 8-week intervals for both nAMD and diabetic macular edema (DME). While the drug shows similar functional and anatomic outcomes with a low adverse effect profile and trial data demonstrating increased treatment duration, its exact place in the VEGF marketplace is yet to be determined. In this article, we discuss the mechanism of action, pivotal clinical trials leading to approval, and the anticipated role for faricimab in the treatment of retinal neovascular disease.Keywords: neovascular age-related macular degeneration, nAMD, macular degeneration, anti-vascular endothelial growth factor, anti-VEGF, faricimab, choroidal neovascularization, CNVM